High-strength copper-based alloy with excellent resistance to hydrogen embrittlement. (7th September 2016) - Yamabe, Junichiro; Takagoshi, Daiki; Matsunaga, Hisao; Matsuoka, Saburo; Ishikawa, Takahiro; Ichigi, Takenori
Abstract: High-pressure components are generally designed with safety factors based on the tensile strength (TS) of the material; accordingly, materials with higher TS permit designed components with thinner walls, which reduce the weight and cost of the parts. However, many high-strength metals are severely degraded by hydrogen. To this point, efforts to develop a high-strength metal with a TS far beyond 1000 MPa and excellent resistance to hydrogen embrittlement (HE) have failed. This study introduces a high-strength metal with an excellent HE resistance, composed of a precipitation-hardened copper-beryllium alloy with the TS of 1400 MPa. Slow strain rate tensile (SSRT) tests of both smooth and notched specimens were performed in 115-MPa hydrogen gas at room temperature (RT). The alloy had a relative reduction in area RRA ≈ 1 and a relative notch tensile strength RNTS ≈ 1, without degradation in either characteristic. Highlights: Precipitation-hardened copper-beryllium alloy was tested. The tensile strength of this alloy in air at room temperature was 1400 MPa. Slow strain rate tensile test was performed in 115-MPa hydrogen gas. No relative area or notch reduction was observed with hydrogen exposure. Tested alloy shows excellent hydrogen embrittlement resistance and high-strength.